Noncoding RNAs Interactions in Hepatic Stellate Cells during Hepatic Fibrosis - Siti Aishah Sulaiman; Vicneswarry Dorairaj; Khairun Nur Abdul Ghafar; Nor Azian Abdul Murad (Livers, 2021)
Hepatic fibrosis is a reversible wound healing process following liver injury. Although this process is necessary for maintaining liver integrity, severe excessive extracellular matrix accumulation (ECM) could lead to permanent scar formation and destroy the liver structure. The activation of hepatic stellate cells (HSCs) is a key event in hepatic fibrosis. Previous studies show that most antifibrotic therapies focus on the apoptosis of HSCs and the prevention of HSC activation. Noncoding RNAs (ncRNAs) play a substantial role in HSC activation and are likely to be biomarkers or therapeutic targets for the treatment of hepatic fibrosis. This review summarizes and discusses the previously reported ncRNAs, including the microRNAs, long noncoding RNAs, and circular RNAs, highlighting their regulatory roles and interactions in the signaling pathways that regulate HSC activation in hepatic fibrosis.